The Puzzle of Reconciliation after Genocide and the Role of Social Identities: Evidence from Burundi and Rwanda - Theresa Reinold (University of Duisburg-Essen, Käte Hamburger Kolleg / Centre for Global Cooperation Research (KHK/GCR21), 2019)
The question of how societies emerging from genocide manage to return to normalcy, restore social relationships and lay the foundation for sustainable peace, is a puzzling one. The guiding hypothesis underlying this research paper is that identity politics are a key factor for explaining the successes and failures of reconciliation processes. We still know very little about the causal mechanisms underlying reconciliation, one of the reasons for this being the near-total absence of interdisciplinary work on this issue. However, one cannot fully grasp reconciliation dynamics – which play out at the micro- and macro-levels – without synthesizing insights from different disciplines. The paper compares two post-genocide societies – Burundi and Rwanda – which have adopted extremely different approaches to identity politics and reconciliation. Whereas imposing a superordinate identity in a top-down process has not been very effective in either case, there is some evidence suggesting that bottom-up cooperation has been rather successful in promoting reconciliation in Rwanda. Transitional justice in turn plays an ambivalent role. It seems that TJ can only be effective if it is perceived as being applied in an even-handed fashion, and if the political environment is supportive of accountabilityseeking. Neither condition is entirely fulfilled in Rwanda or Burundi.
urn:nbn:de:hbz:464-20191025-150425-7
Keywords: 320; reconciliation; conflict resolution; genocide; transitional justice; social identity theory; self-categorization theory; post-conflict; Ruanda; Burundi; micro-macro level